2013
DOI: 10.1210/en.2012-1802
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone-Related Protein Is a Mitogenic and a Survival Factor of Mesangial Cells from Male Mice: Role of Intracrine and Paracrine Pathways

Abstract: Glomerulonephritis is characterized by the proliferation and apoptosis of mesangial cells (MC). The parathyroid-hormone related protein (PTHrP) is a locally active cytokine that affects these phenomena in many cell types, through either paracrine or intracrine pathways. The aim of this study was to evaluate the effect of both PTHrP pathways on MC proliferation and apoptosis. In vitro studies were based on MC from male transgenic mice allowing PTHrP-gene excision by a CreLoxP system. MC were also transfected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 58 publications
6
41
0
Order By: Relevance
“…Finally, we showed that ERK1/2, p38 MAPK, and PI3‐kinase inhibitors completely abolished the effect on PTHrP‐induced colonic cell proliferation. Several evidences demonstrate that these signaling pathways are involved in the anti‐apoptotic effects exerted by PTHrP through a paracrine pathway [Hochane et al, ; Lezcano et al, ]. Herein we prove the first evidence, to our knowledge, that ERK1/2, p38 MAPK, and PI3‐kinase are also involved in the mitogenic action of exogenous PTHrP (1–34) fragment on Caco‐2 cells.…”
Section: Discussionsupporting
confidence: 59%
“…Finally, we showed that ERK1/2, p38 MAPK, and PI3‐kinase inhibitors completely abolished the effect on PTHrP‐induced colonic cell proliferation. Several evidences demonstrate that these signaling pathways are involved in the anti‐apoptotic effects exerted by PTHrP through a paracrine pathway [Hochane et al, ; Lezcano et al, ]. Herein we prove the first evidence, to our knowledge, that ERK1/2, p38 MAPK, and PI3‐kinase are also involved in the mitogenic action of exogenous PTHrP (1–34) fragment on Caco‐2 cells.…”
Section: Discussionsupporting
confidence: 59%
“…Also of note, antiapoptotic effects have been reported in the same osteoblastic cell type used herein, but stably transfected with a PTH1R plasmid construct (35). In addition, other studies have reported that cell protection by PTHrP may be conferred through the autocrine/ paracrine pathway in renal cells and other osteoblastic cell types (39,41,46). Consistent with previous findings in osteoblasts and other cell types (47,48), we here observed PTH1R protein down-regulation in PTHrP-overexpressing MC3T3-E1 cells, related to receptor internalization.…”
Section: Discussionsupporting
confidence: 56%
“…The mice and rats were sacrificed immediately after the Trimeresurus flavoviridis or OX-7 mAb injection at 3, 5, 7, or 14 days after GN induction. At each time point, following euthanasia, renal tissue was obtained, and glomeruli were isolated by differential sieving (22, 23). The cortex was subsequently cut off with a fine pair of surgical scissors and placed in a plastic Petri dish that contained PBS buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The cortex was subsequently cut off with a fine pair of surgical scissors and placed in a plastic Petri dish that contained PBS buffer. The cortex was forced through sequential sieving (150, 106, and 75 μm for the rats; 125, 71, and 53 μm for the mice at room temperature (23, 24). The glomeruli were collected on the sieve (75 μm for the rats, 53 μm for the mice) using cold PBS buffer, centrifuged at 1,000 rpm for 5 min in a clinical centrifuge, resuspended in 5 ml of cold PBS buffer, and assessed for purity (more than 95% glomeruli, Figure S1) under the microscope.…”
Section: Methodsmentioning
confidence: 99%